Historical road system and farmhouses in Apulia - L.P. Caliandro; R.V. Loisi; P. Dal Sasso (Journal of Agricultural Engineering, 2013)
Human settlements often originate from the presence of such natural sustaining water bodies as springs, rivers, or rather from the proximity of relevant infrastructure (roads, harbours, etc.). Rural residential buildings, however, are generally closely linked to the cultivated fields of a farm. A significant example of rural buildings, that particularly identifies some national or regional areas, is that of the Apulian farmhouses known as “masserie”, which are considered as an important cultural heritage in the rural territories of that region. These buildings, featuring relevant architectural and landscape characteristics, encompass several functions within them and often host more than one family living there permanently. Territorial distribution of rural buildings and farmhouses in Apulia is diversified and, in general and as already stated, it can depend on the close relationship between the building and its adjacent agricultural lot. Moreover, in the case of the Apulian farmhouses, owing to their specific role in overseeing the territory and asserting land tenure rights, this distribution may have “genetic” origins influenced by other elements, too. The efforts of the present work regarding this issue are to investigate the existing relationships between the Apulian farmhouses system and the “historical” roads already existing when they were built (XII-XIX centuries). Particularly, the study proved if there are any correlations among the Roman roads, the sheep’s paths (tratturi) crossing the Apulia region and the farmhouses, both from the point of view of the distance from the roads and the importance of the individual farmhouses. Using GIS software and overlay mapping procedures it was possible to quantify the amount of farmhouses and their concentration within the catchment areas of the aforementioned historical roads, while through historical and territorial in-depth analysis those elements characterizing the most interesting farmhouses from the historical and architectural point of view were identified. The research provided interesting information on the existing relations between historical roads and farmhouses, leading to further considerations on the possibility to enhance some of these monuments, located in rural areas, through the promotion of the “integrated” asset represented by the historical road system, with particular reference to the sheep’s paths (tratturi).